A man takes a step forward with probability 0.4 and backward with probability 0.6 . Find the Probability at the end of eleven steps he is one step away from starting point.
To try more such problems click here .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The man has to finish one step away from starting point so he has either taken:
5 steps forward and 6 steps back
Or 6 steps forward and 5 steps back
For each arrangement of 5 steps forward and 6 steps back, the probability of that happening is:
( 0 . 4 ) 5 x ( 0 . 6 ) 6
And there are 11C5 ways to place the 5 forward steps within the 11 steps so the total probability for this case is:
( 0 . 4 ) 5 x ( 0 . 6 ) 6 x (11C5)
And for each arrangement of 6 steps forward and 5 steps back the probability is:
( 0 . 4 ) 6 x ( 0 . 6 ) 5
And there are 11C6 ways to place the 6 forward steps (which is equal to 11C5 ways to place the backward steps) so the probability of this case is:
( 0 . 4 ) 6 x ( 0 . 6 ) 5 x (11C6)
So the total probability is the two cases added together which equals:
( ( 0 . 4 ) 5 x ( 0 . 6 ) 6 x (11C5)) + ( ( 0 . 4 ) 6 x ( 0 . 6 ) 5 x (11C6)) = 0 . 3 7 to 2dp.
Problem Loading...
Note Loading...
Set Loading...
Since the man is one step away from starting point it means that either
(i) man has taken 6 steps forward and 5 steps backward.
(ii) man has taken 5 steps forward and 6 steps backward.
Taking movement of 1 step forward as success and movement of 1 step backward as failure.
p = Probability of success = 0.4
q = Probability of failure = 0.6
Applying Binomial Theoram, R e q u i r e d p r o b a b i l i t y = P ( X = 6 t o X = 5 ) = P ( X = 6 ) + P ( X = 5 ) = ( 6 1 1 ) p 6 q 5 + ( 5 1 1 ) p 5 q 6 = ( 5 1 1 ) ( p 6 q 5 + p 5 q 6 ) = 1 . 2 . 3 . 4 . 5 1 1 . 1 0 . 9 . 8 . 7 [ ( 0 . 4 ) 6 ( 0 . 6 ) 5 + ( 0 . 4 ) 5 ( 0 . 6 ) 6 ] = 0 . 3 7